A CLINICAL CASE OF TICK-BORNE ENCEPHALITIS WITH EXTRAPYRAMIDAL SYMPTOMS - Бахтеева, Александра Викторовна; Зуева, Светлана Алексеевна; Елгина, Светлана Ивановна; Семенов, Владимир Александрович; Рохленко, Ольга Валерьевна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна (Medicine in Kuzbass, 2025)
Kemerovo region is an endemic area for the incidence of tick-borne viral encephalitis (CVE). The morbidity rate of the population of Kuzbass in 2023 was 3.1 times higher than the incidence rate in the Russian Federation. In 2023, the incidence increased by 7.6% (the total number of patients was 98). The proportion of encephalitic forms of CVE was 18.4% (2022 – 15.2%), meningeal – 23.5% (2022 – 14.1%), febrile – 58.1% (2022 – 70.7%). 4 fatal cases have been registered. This article is devoted to a rare case of tick-borne viral encephalitis with the development of akinetic-rigid syndrome in the acute period of the disease.